Effect of renal denervation on urine angiotensinogen excretion in prenatally programmed rats. Issue 20 (19th October 2017) - Mansuri, Asifhusen; Legan, Susan K.; Jain, Jyoti; Alhamoud, Issa; Gattineni, Jyothsna; Baum, Michel
Abstract: Prenatal programming results in an increase in blood pressure in adult offspring. We have shown that compared to control adult offspring whose mothers were fed a 20% protein diet, programmed adults whose mothers were fed a 6% protein diet during the last half of pregnancy have an increase in renal sympathetic nerve activity and urinary angiotensinogen/creatinine levels. We hypothesized that the increase in urinary angiotensinogen was mediated by renal sympathetic nerve activity in programmed rats. In this study performed in 3 month old rats, renal denervation resulted in normalization of blood pressure in the 6% programmed group (150 ± 3 Hg in 6% sham vs. 121 ± 4 Hg in 6% denervated, P < 0.001), and a reduction in blood pressure in the 20% group (126 ± 2 Hg 20% sham vs. 113 ± 4 Hg 20% denervated ( P < 0.05). We confirm that the intrarenal renin–angiotensin system assessed by urinary angiotensinogen/creatinine is upregulated in offspring of rats fed a 6% protein diet rats compared to 20% controls. To determine if sympathetic nerve activity was mediating the increase in urinary angiotensinogen in programmed rats, we compared denervated to sham‐operated control and programmed rats. Renal denervation had no effect on urinary angiotensinogen/creatinine ratio in the 20% group and no effect on the increased urinary angiotensinogen/creatinine ratio found in programmed rats. This study demonstrates that the increase in urinary angiotensinogen in programmed rats is not mediated by renal sympathetic nerve activity. Abstract : We have demonstrated that prenatal programming is associated with an increase in renal sympathetic nerve activity and an increase in the intrarenal renin–angiotensin system. This manuscript examines if the increased renal sympathetic nerve activity in programmed rats mediates the increase in urinary angiotensinogen, a marker for the intrarenal RAS.